How to GAN event subtraction - Butter, Anja; Plehn, Tilman; Winterhalder, Ramon (SciPost Physics Core, 2020)
SciPost Journals Publication Detail SciPost Phys. Core 3, 009 (2020) How to GAN event subtraction